Evaluación del desarrollo clínico psicomotriz de recién nacidos prematuros, de la UCIN, en un hospital del MINSA, Punchana - 2020 - Ruiz Garcia, Andres Gabino (2022)
Annually 15 million premature infants are born, which in the last 30 years, its percentage is estimated between 5 and 7%. However, complications related to it have been responsible for approximately one million deaths. To this is added the greater susceptibility of having problems during the neonatal period, increasing their risk of morbidity and mortality even beyond the first months of life; as well as, the readmission rates of late preterm newborns that are 1.5 to three times higher than those of term newborns, in addition to being vulnerable to presenting some type of disability such as intellectual, motor and sensory level. Objective: To determine the relationship between the evaluation of psychomotor clinical development (motor disability, sensory disability, learning difficulties) and premature newborns in the Neonatal Intensive Care Unit in a MINSA Hospital, 2020. Materials and methods: the study It has a nonexperimental, quantitative, observational, analytical correlational, retrospective design. The study population will be assessed with the "Peruvian Test for the evaluation of the development of the child in infants and in premature Capurro", correlated with prenatal, natal and postnatal clinical history from which information on the child's psychomotor development will be obtained.